Frequency Distribution of Antimalarial Drug Resistance Alleles among Plasmodium falciparum Isolates from Gezira State, Central Sudan, and Gedarif State, Eastern Sudan - Menegon, Michela (The American Society of Tropical Medicine and Hygiene, 2010)
In 2004, Sudan adopted artesunate + sulfadoxine/pyrimethamine (SP) combination as the first-line drug, in response to the high level of falciparum resistance to antimalarials. In 2007, a molecular study on antimalarial resistance linked genes, pfcrt, pfmdr1, pfdhfr, pfdhps, and pfATPase6, was conducted on 198 isolates from central and eastern Sudan. We observed a high frequency of point mutations at almost all loci analyzed, mainly of pfcrt 76T (72.7%), pfdhfr 51I (75.3%), and pfdhfr 108N (72.7%) alleles. The MARK III in vitro test for chloroquine sensitivity in 45 P. falciparum isolates showed that 37.8% of the isolates were low resistant and 6.7% were fully resistant. This study represents the most recent molecular investigation on antimalarial resistance in this area after the adoption of artemisinin-based combination therapy (ACT), and underlines the importance of the analysis of SP resistance evolution to monitor the efficacy of ACT therapy in endemic areas.